Design of Control Jig for Inserts Measurement - Mrkvica, Ivan; Sleha, Vojtech; Petru, Jana; Neslusan, Miroslav; Jurko, Jozef; Panda, Anton (Manufacturing Technology Journal, 2016)
This paper aims to design a control jig for cutting inserts measurement. These inserts are made from standardized inserts by grinding. The control jig is intended to be used on two different types of measuring devices and it has to meet the functional requirements of these devices.The intoduction describes specific functional requirements on the jig, provides information about measuring devices and examples of cutting edges grinded on inserts. Next part describes the design of several variants of jig parts and reasons for their application. Paper is focused specifically on design of jig body variants, description of measuring arm and the way of clamping of inserts in the control jig. The measuring range is described for each of proposed variant. In the closing part of the article particular variants are compared according to their suitability, stability during measuring and range of serviceability for measuring of the inserts.
Keywords: control jig; body; arm; cutting insert